Desafios no atendimento às mulheres vítimas de violência na Atenção Primária à Saúde: uma revisão integrativa de literatura. - Fabricia Voieta da Silva Teixeira (2024)
Violence against women is a social phenomenon and is an important public health problem. Even though the incidence of the problem is increasing, evidence points to the existence of underreporting of cases and that some women do not even seek assistance. Bearing in mind that Primary Care is a gateway to health care and that the notification of violence and the comprehensive care of victims are competencies of health professionals - even if in conjunction with other care services - this study aims to objective to identify the challenges faced by PHC in offering care to women victims of violence. To achieve this objective, an Integrative Literature Review was carried out to investigate the most recent evidence about the problem. The bibliographic research consisted of searching for articles published between 2017 and 2023 in the CAPES and VHL databases, using the descriptors “Violence against Women”, “Primary Health Care”, “Sistema Único de Saúde”. As a result of the research, 22 articles were found that met the eligibility criteria. According to the findings, the main challenges faced by PHC professionals were identified as: factors related to the social representation of violence, the feeling of fear and insecurity regarding the aggressor's reprisals, work overload, the need for professional training and interventions institutions to guarantee an adequate structure for assistance. It is concluded that, although some women experience a repetitive cycle of violence, associated with fear and financial dependence, among other factors, effective reception and prevention actions are very important to interrupt this cycle, contributing both to the reduction of other morbidities and for the development of strategies capable of promoting the resumption of their lives.